Lapp reindeer movements across the frontiers of northern Scandinavia - Elbo, J. G. (Polar Record, 1952)
The present northern border of Norway and Sweden was fixed by treaty in 1751 between the United Kingdom of Denmark-Norway and the Kingdom of Sweden, then including Finland. Previous attempts to determine the frontier had failed, largely because of intermittent warfare over a long period between Denmark and Sweden. A codicil to the 1751 treaty laid down the rights of the Lapps in the frontier region and it was expressly stated that movement over the frontier would be permitted according to old usage. The usage here referred to was the movement of Swedish Lapps with their reindeer into Norway for pasture during the summer, and a similar movement of Norwegian Lapps with their reindeer into Sweden for pasture during the winter. The majority of the Norwegian Lapps entering Swedish territory went into Finland. In addition, a few Norwegian Lapps further south, in the present Nord Trøndelag Fylke, traditionally moved into Jämtland in Sweden during the summer.